Memahami Tradisi Spiritualitas Pesantren: (Sebuah Analisis Sosio-Historis terhadap Spiritualitas Pesantren di Indonesia) - Mujab, Saiful (Prodi Sosiologi Agama, 2017)
This project involves discovering how spiritual tradition exists in the pesantren in Indonesia. The goal of this research proves the phenomenon that pesantren and spirituality traditions are strongly linked and connected. Several spiritualities in pesantren are; thoriqoh, tirakat, ijazahan, and others. This article is arranged based on library research and comparing several references by some books, articles, and journals. Furthermore, this research also takes some of the experiences of some people who ever study, live, and experience the pesantren tradition in Indonesia (especially in Java). In conclusion, this article tries to explore the argumentation historically and socially that Pesantren and spiritualism have a strong correlation from the beginning of Islamic spreading in Indonesia.